The Two Languages of a City in the Works of Juan Carlos Onetti - Ju. A. Larikova (Ибероамериканские тетради, 2024)
When Juan Carlos Onetti (1909–1994), a young Uruguayan writer arrived in Buenos Aires in 1930, he was so dazzled by the emerging metropolis that he made it the main setting for his works over the following two decades. Literary theory explores this «experimental» stage of Onetti’s writing, marked by cosmopolitanism, cinematic effects, and a language susceptible to urban social dynamics, as well as the later stage when Onetti created the imaginary city of Santa María, similar to Faulkner’s world of Yoknapatawpha in its narrative potential. Nevertheless, what seems the most interesting is the precise moment when the author decided to change the setting for his work as he found himself tired of the Buenos Aires theme and its aesthetic. The article focuses on the novel A Brief Life (1950) and the short novel A Grave with No Name (1959), whose storylines cross in the two cities, Santa Maria and Buenos Aires. Regardless of the technical aspects of such a shift, it reveals the volatility of a modern city whose history is captured in fiction.